2020
DOI: 10.1017/s0142716420000570
|View full text |Cite
|
Sign up to set email alerts
|

The impact of older siblings on the language environment and language development of bilingual toddlers

Abstract: Previous research has suggested that the language development of bilingual children benefits from more exposure and opportunities for language use. Typically, this research has used aggregated measures of exposure and use. The role of specific interlocutors and in particular older siblings has received comparatively little attention. In this study, we examine the impact of having an older sibling on the language environment and language development of a group of 31 bilingual Greek–Dutch toddlers aged 16 to 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 49 publications
1
10
1
1
Order By: Relevance
“…Regardless of whether they are developing typically or atypically, children's caregivers play a key role in providing crucial language experience (Casillas et al, 2020; De Houwer, 2007; Tsinivits & Unsworth, 2021). For example, the amount of infant-directed speech (Ramírez-Esparza et al, 2014) and turn-taking that children experience (Donnelly & Kidd, 2021) predicts their speech and language development.…”
Section: Bilingual Language Experience From Caregiversmentioning
confidence: 99%
“…Regardless of whether they are developing typically or atypically, children's caregivers play a key role in providing crucial language experience (Casillas et al, 2020; De Houwer, 2007; Tsinivits & Unsworth, 2021). For example, the amount of infant-directed speech (Ramírez-Esparza et al, 2014) and turn-taking that children experience (Donnelly & Kidd, 2021) predicts their speech and language development.…”
Section: Bilingual Language Experience From Caregiversmentioning
confidence: 99%
“…Beispielsweise scheint auch die Sprachnutzung durch Geschwister Auswirkungen auf den Spracherwerb mehrsprachiger Kinder zu haben. So zeigen sich etwa bei mehrsprachig aufwachsenden Kindern im Vorschulalter etwa Zusammenhänge zwischen ihren Sprachleistungen in der Umgebungssprache und der Nutzungshäufigkeit der Umgebungssprache durch ältere Geschwister Sorenson-Duncan & Paradis, 2020;Tsinivits & Unsworth, 2021). Neben der familiären Sprachnutzung und dem sprachlichen Input, den ein Kind erfährt, ist auch der Sprachgebrauch des Kindes selbst ein wichtiger Einflussfaktor für den Spracherwerb.…”
Section: Diskussionunclassified
“…Rodina et al ( 2020 ) showed that several language-external factors such as family type (mixed family vs. HL-speaking parents), age, and current exposure to HL instruction are related to the HL development of grammatical gender in HL speakers with various SL properties. In contrast, Tsinivits and Unsworth ( 2021 ) showed that having an older sibling is related to the increased input of SL in the home setting, and hence higher SL abilities, yet having an older sibling was reported to have no effect on HL grammatical complexity. It should be noted that the input/exposure factors are related to language dominance/proficiency—children with more exposure/input to the language show higher dominance in that language (e.g., Treffers-Daller, 2019 ).…”
Section: Introductionmentioning
confidence: 95%